Utilization of Encapsulated Seabuckthorn and Spirulina for the Development of Functional Bread - , Skarma Choton, Julie D Bandral, Monika Sood, Neeraj Gupta, Upma Dutta (Archives of Current Research International, 2025)
Bread is one of the staple foods and largely consumed throughout the globe. Seabuckthorn (Hippophae rhamnoides L.) is rich in nutrients and bioactive compounds possess numerous health benefits. Spirulina also known as ‘Food of the future’ is source of good quality protein, fiber and other nutrients. The aim of the study was to develop bread from encapsulated seabuckthorn and spirulina powder and to evaluate the proximate composition of bread. The result showed that the colour L*, a* and b* value of bread increases with increases encapsulated seabuckthorn at 2.5, 5, 7.5, 10, 12.5 and 15%. The loaf weight and volume also increase while the specific volume and crust to crumb ratio decreases with addition of encapsulated seabuckthorn (2.5, 5, 7.5, 10, 12.5 and 15%) and spirulina powder (3%) in the bread. The addition of encapsulated seabuckthorn (2.5, 5, 7.5, 10, 12.5 and 15%) and spirulina powder (3%) in the bread increased the crude protein content, ash, crude fat, crude fiber, carbohydrate whereas the moisture, water activity and energy decreased. The study has shown that the functional bread can be developed from encapsulated seabuckthorn and spirulina powder which would enhance the nutrition and prevent malnutrition.